FORMATION OF INTERCULTURAL COMMUNICATIVE COMPETENCE THROUGH MULTIMODAL RESOURCES AND PROJECT-BASED LEARNING - Yerkinkyzy Zh.; Akmadi M.A. (Research Retrieval and Academic Letters, 2026)
This study examines how integrating multimodal resources and project-based learning in English as a Foreign Language education develops intercultural communicative competence. It specifically investigates how these educational strategies foster learners’ intercultural awareness, communicative skills, and engagement, and it identifies essential pedagogical conditions for their effective use. Using a systematic review of 190 peer-reviewed publications from Scopus (2005–2025) and the PRISMA methodology, the research aims to clarify the impact of innovation in digital tools and project-based methods on ICC development. The review finds that integrating multimodal resources and project-based learning is effective for cultivating ICC as a key objective in modern language education. Bibliometric and keyword analyses reinforce the view that ICC is multidimensional and deeply connected to language learning, communication, and cultural understanding. The evidence consistently shows that multimodal tools advance learners’ cognitive processing, motivation, and cultural interpretation skills, while project-based learning enhances collaboration, critical thinking, and real-world intercultural interactions. Together, these approaches create dynamic, student-centered environments that maximize the development of linguistic and intercultural competencies. Success relies on factors such as teachers’ digital competence, instructional design, and appropriate scaffolding. The findings highlight that intentional integration of digital tools is essential for meaningful learning outcomes in EFL, underpinning the study’s argument that innovative pedagogical strategies are vital for advancing ICC in global and digital contexts.